Analyst following, staggered boards, and managerial entrenchment - Jiraporn, Pornsit; Chintrakarn, Pandej; Kim, Young S. (Journal of Banking & Finance, 2012)
We use agency theory to explore how analyst coverage is influenced by the managerial entrenchment associated with the staggered board. The evidence suggests that firms with staggered boards attract significantly larger analyst following. We also document that firms with staggered boards experience less information asymmetry. Staggered boards insulate managers from the discipline of the takeover market. Entrenched managers are well-protected by the staggered board and have fewer incentives to conceal information, resulting in less information asymmetry. The more transparent information environment facilitates the analyst’s job. As a consequence, more analysts are attracted to firms with staggered boards. We also document the beneficial role of analyst coverage in improving firm value. Our results confirm the notion that analysts, as information intermediaries, provide oversight over management and thus help alleviate agency conflicts. The positive effect of analyst coverage, however, is severely reduced when the firm has a staggered board in place.